Long-term seizure outcome after epilepsy surgery of neuroglial tumors - Rácz, Attila; Müller, Philipp; Becker, Albert; Hoffmann, Nico; Rüber, Theodor; Borger, Valeri; Vatter, Hartmut; Surges, Rainer; Elger, Christian E. (Frontiers in Neurology, 2024)
Purpose: Neuroglial tumors are frequently associated with pharmacorefractory epilepsies. However, comprehensive knowledge about long-term outcomes after epilepsy surgery and the main prognostic factors for outcome is still limited. We sought to evaluate long-term outcomes and potential influencing factors in a large cohort of patients who underwent surgery for neuroglial tumors in a single-center setting. Methods: The study analyzed the outcomes of 107 patients who underwent epilepsy surgery for neuroglial tumors between 2001 and 2020 at the Department of Epileptology, University Hospital Bonn, in Germany. The outcomes were evaluated using Engel classification. Differences in outcome related to potential prognostic factors were examined using the Chi2-test, Fisher's exact test and sign-test. Additionally, stepwise logistic regression analysis was employed to identify independent prognostic factors. Results: Complete seizure freedom (Engel Class IA) was achieved in 75% of the operated patients at 12 months, and 56% at the last follow-up visit (70.4 ± 6.2 months, median: 40 months). Completeness of resection was a crucial factor for both 12-month follow-up outcomes and the longest available outcomes, whereas lobar tumor localization, histology (ganglioglioma versus dysembryoplastic neuroepithelial tumor), history of bilateral tonic-clonic seizures prior to surgery, invasive diagnostics, side of surgery (dominant versus non-dominant hemisphere), age at epilepsy onset, age at surgery, and epilepsy duration did not consistently impact postsurgical outcomes. Among temporal lobe surgeries, patients who underwent lesionectomy and lesionectomy, including hippocampal resection, demonstrated similar outcomes. Conclusions: Neuroglial tumors present as excellent surgical substrates in treating structural epilepsy. To achieve an optimal postsurgical outcome, a complete lesion resection should be pursued whenever possible.